The complete family office handbook : a guide for affluent families and the advisers who serve them - Rosplock, Kirby, 1974- (Bloomberg financial series., 2014)
"Everything you need to take advantage of today's most exciting new wealth management career options. It seems like ever since Oprah started hers, family offices are all the rage among today's high-net-worth individuals. Private wealth management advisory firms serving one client, or a very limited number of exclusive clients, family offices come in two flavors: single family and multifamily, with the latter operating more like a traditional wealth management practice. If you're like most financial advisors, by now you're familiar with the concept, but don't know if it's right for you and your clients, or how to break into the business. This book supplies you with answers to all your questions about this exciting new career opportunity. Demystifies the concept of the family office, clarifying who should consider joining a multi-family office or starting their own single-family office Explains what services should be rendered by a family office and what the expense to the family can be. Provides the most current knowledge, research, and cutting-edge approaches from thought leaders in the family office industry. Gives you practical tools, templates, and exercises to guide you as you envision, plan, and develop your family office"--